Short term attachment at SCUN (7-24 july 2009) - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Muhammad Najib, Muhammad Nor (Penerbit UMP, 2009)

(untitled)
South-Central University for Nationalities (SCUN) in Wuhan, China, was established by the Chinese Government in l 951 as a notional university.